2016
DOI: 10.1002/hep.28753
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of guideline‐tailored therapy with direct‐acting antivirals for hepatitis C virus‐associated mixed cryoglobulinemia

Abstract: Interferon-free, guideline-tailored therapy with direct-acting antivirals is highly effective and safe for HCV-associated MC patients; the overall 100% rate of clinical response of vasculitis, on an intention-to-treat basis, opens the perspective for curing the large majority of these so far difficult-to-treat patients. (Hepatology 2016;64:1473-1482).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
177
2
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(199 citation statements)
references
References 50 publications
(119 reference statements)
11
177
2
3
Order By: Relevance
“…Sustained virological response is the main goal in these patients since clinical remission of vasculitis is closely associated with viral clearance 8 . Few studies have reported promising results on the effectiveness and tolerance of direct acting antiviral drugs (DAA), either in association with interferon (IFN) or using IFN-free regimens [8][9][10][11] . The aim of the present study was to evaluate effectiveness and tolerance of an all oral IFN-and ribavirin-free regimen with sofosbuvir plus daclatasvir in patients with cryoglobulinemia vasculitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained virological response is the main goal in these patients since clinical remission of vasculitis is closely associated with viral clearance 8 . Few studies have reported promising results on the effectiveness and tolerance of direct acting antiviral drugs (DAA), either in association with interferon (IFN) or using IFN-free regimens [8][9][10][11] . The aim of the present study was to evaluate effectiveness and tolerance of an all oral IFN-and ribavirin-free regimen with sofosbuvir plus daclatasvir in patients with cryoglobulinemia vasculitis.…”
Section: Introductionmentioning
confidence: 99%
“…Median time to achieve a clinical response was twelve weeks. forty four patients treated by sofosbuvir based IFN-free regimen which included ribavirin in twenty eight patients 9 . All patients were virological responders and 93% improved M A N U S C R I P T Clearance of cryoglobulin is an important goal of the treatment of HCV-CryoVas.…”
Section: Introductionmentioning
confidence: 99%
“…For at least some patients with severe cryoglobulinemia achievement of SVR may be insuffi cient to complete mitigate its manifestations, and additional support with rituximab and/or plasmapheresis may still be required. However, this report and others indicate that inferior SVR rates in HCV patients with cryoglobulinemia have been overcome with DAA therapy ( 8,9 ), and that clinical improvement, although not inevitable, typically follows. Th e enhanced effi cacy of DAA has simplifi ed management of this important manifestation of HCV infection.…”
mentioning
confidence: 66%
“…The available data suggest that IFN-free regimens are safe, generally well-tolerated, and effective in MC patients [140][141][142][143]. In the IFN era, rituximab was administered mostly to patients who had failed or were not eligible for antiviral therapy, even if a rituximab plus antiviral combination was suggested for patients with severe manifestations (generally using rituximab before antiviral therapy) [132,[144][145][146].…”
Section: Extrahepatic Manifestations Of Hcv: Mixed Cryoglobulinemiamentioning
confidence: 99%